2023
DOI: 10.3390/s23031503
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Embroidered Textile Strain Sensors: An Alternative to Stitch-Based Strain Sensors

Abstract: Smart textile sensors have been gaining popularity as alternative methods for the continuous monitoring of human motion. Multiple methods of fabrication for these textile sensors have been proposed, but the simpler ones include stitching or embroidering the conductive thread onto an elastic fabric to create a strain sensor. Although multiple studies have demonstrated the efficacy of textile sensors using the stitching technique, there is almost little to no information regarding the fabrication of textile stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…11 A strain/pressure sensor is capable of converting impact of strain/pressure into electrical signal, usually capacitance or resistance change. 12 Such a change of resistance when the material is strained is inversely proportional to the © 2024 Vietnam Academy of Science and Technology and Wiley-VCH GmbH. cross-sectional area being impacted, and proportional to the length of the affected areas on the materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 A strain/pressure sensor is capable of converting impact of strain/pressure into electrical signal, usually capacitance or resistance change. 12 Such a change of resistance when the material is strained is inversely proportional to the © 2024 Vietnam Academy of Science and Technology and Wiley-VCH GmbH. cross-sectional area being impacted, and proportional to the length of the affected areas on the materials.…”
Section: Introductionmentioning
confidence: 99%
“…cross-sectional area being impacted, and proportional to the length of the affected areas on the materials. 12 To date, many different kinds of materials have been applied to strain/pressure sensors such as silicone, semiconductors, 13 nanoparticles, 14 nanowires, 15 which have made huge progress in fabrication of strain/pressure sensor with dramatic decrease in the component size that results in convenient components and devices. A variety of principles including piezoresistivity, capacitance, piezoelectricity and triboelectricity can be introduced in this section, which is based on the transduction mechanism accordingly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ease on the manufacturability of stitched and embroidered structures allows for a mass production of textile sensors without compromising their cost and reproducibility. 13 Electrical properties of embroidered structures with conductive threads depend on numerous parameters, as it was shown by Zheng et al, 14 who conducted an overlay plot analysis to predict the change in the electrical resistance by changing embroidering speed, stitch length, needle thread pre-tension, and embroidering direction. It was observed that the combined output of stitch length and embroidery speed can affect largely the electrical parameters for the fabrication of e-textiles, such as high-performance circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ease on the manufacturability of stitched and embroidered structures allows for a mass production of textile sensors without compromising their cost and reproducibility. 13…”
Section: Introductionmentioning
confidence: 99%